Performance analyses of Cu–Cl hydrogen production integrated solar parabolic trough collector system under Algerian climate. (8th February 2018) - Ouagued, Malika; Khellaf, Abdallah; Loukarfi, Larbi
Abstract: The potential of hydrogen production by thermochemical cycle in Algeria using solar radiation as heat sources is estimated under the climate conditions of the country. The study analyzes an integrated copper–chlorine (Cu–Cl) thermochemical cycle with solar parabolic trough system for hydrogen production. In order to determine the most promising solar sites available for deploying the integrated system, the direct normal solar irradiance (DNI) for horizontal tracking system oriented in North-South has been estimated and compared for different locations. Heat gain from parabolic trough collector model is evaluated under Algerian conditions. To describe the different steps of the Cu–Cl cycle for hydrogen production, we perform a thermodynamic analysis accounting for relevant chemical reactions and including the determination of the energy necessary to the cycle. A parametric study is conducted to investigate the effect of heat gain from the parabolic trough collector (PTC) on the hydrogen production rate. Furthermore, the rate production of hydrogen by the Cu–Cl cycle is analyzed and compared for performance improvement of the system for different climatic regions in Algeria. Simulation results reveal great opportunities of hydrogen production using Cu–Cl cycle combined with solar PTC in the south of Algeria with annual hydrogen production exceeds 84 Tons H2 /year (around 0, 30 kg/m 2 /day). Highlights: Based on Hotel model, direct solar radiation has been estimated at different climatic regions in Algeria. Energy performance of parabolic trough collector was evaluated by simulation of energy conversions from solar energy. Thermodynamic analysis of Cu–Cl cycle including determination of energy and exergy efficiencies was described. Hydrogen production was compared with results obtained by other research for performances improvement of the system. Around 0, 30 kg/m 2 /day of hydrogen can be produced in the south of Algeria by Cu–Cl cycle combined with solar PTC.